Identifying the use of code switching In Malaysian Educational Comedy Series titled Oh My English! - Nur Adilah Mohd Subkhi,; Azianura Hani Shaari, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2021)
Code-switching normally takes place amongst bilingual or multilingual speakers. This is because both bilingual and multilingual speakers have a high tendency to alternate between two or more languages, or language varieties, in any context of a single conversation or situation. Other than that, code-switching is also one of the important aspects of sociolinguistic studies. The use of code-switching in the Malaysian Educational Comedy Series entitled Oh My English! has therefore been investigated for this research. This research aims to identify the types of codeswitching that the actors and actresses used in the Oh My English! series and the functions or reasons for each code-switching activity. To achieve this aim, a qualitative method was used to obtain data. Several videos from Oh My English! YouTube channels were identified and selected. Based on the findings, there are different types of code-switching activities used by the actors and actresses in the comedy series. They are, (1) Tag switching, (2) Inter-sentential, and (3) Intra-sentential code switching. Apart from that, 6 different functions of code-switching were found in the analysis. In conclusion, the findings of this study indicated that code switching in Malaysian English comedy is not just an unplanned linguistic strategy, but carries certain purposes that emphasize on the establishment of people’s solidarity and cultural identity.